Inhibition of miR-29 by TGF-beta-Smad3 Signaling through Dual Mechanisms Promotes Transdifferentiation of Mouse Myoblasts into Myofibroblasts - Zhou, Liang (Public Library of Science, 2012)
MicroRNAs (miRNAs) are non-coding RNAs that regulate gene expression in post-transcriptional fashion, and emerging studies support their importance in regulating many biological processes, including myogenic differentiation and muscle development. miR-29 is a promoting factor during myogenesis but its full spectrum of impact on muscle cells has yet to be explored. Here we describe an analysis of miR-29 affected transcriptome in C2C12 muscle cells using a high throughput RNA-sequencing platform. The results reveal that miR-29 not only functions to promote myogenic differentiation but also suppresses the transdifferentiation of myoblasts into myofibroblasts. miR-29 inhibits the fibrogenic differentiation through down-regulating both extracellular matrix genes and cell adhesion genes. We further demonstrate that miR-29 is under negative regulation by TGF-beta (TGF-β)–Smad3 signaling via dual mechanisms of both inhibiting MyoD binding and enhancing Yin Yang 1 (YY1)-recruited Polycomb association. Together, these results identify miR-29 as a pleiotropic molecule in both myogenic and fibrogenic differentiation of muscle cells.